2010
DOI: 10.1016/j.cell.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Bardet-Biedl Syndrome Proteins Assemble a Coat that Traffics Membrane Proteins to Cilia

Abstract: Summary The BBSome is a complex of Bardet-Biedl Syndrome (BBS) proteins that shares common structural elements with COPI, COPII and clathrin coats. Here we show that the BBSome constitutes a coat complex that sorts membrane proteins to primary cilia. Biochemically, the BBSome is the major effector of the Arf-like GTPase Arl6/ BBS3. In vivo, the BBSome and Arl6 localize to ciliary punctae and Arl6GTP is required to target the BBSome to cilia. Congruently, GTP-bound Arl6 and acidic phospholipids are sufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
778
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 558 publications
(810 citation statements)
references
References 55 publications
28
778
3
1
Order By: Relevance
“…3E). This result demonstrates that BBS1 is the BBSome subunit that likely directly interacts with BBS3, consistent with results using in vitro purified proteins (28).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…3E). This result demonstrates that BBS1 is the BBSome subunit that likely directly interacts with BBS3, consistent with results using in vitro purified proteins (28).…”
Section: Resultssupporting
confidence: 77%
“…Indeed, phenotypic characterization of Bbs3 −/− mice revealed that they developed retinal degeneration and are male-infertile because of the absence of sperm flagella. Consistent with these phenotypic similarities, our biochemical analysis demonstrates that BBS3 interacts with the BBSome and is required for the ciliary localization of the BBSome, confirming in vitro data published recently (28). Furthermore, we showed that mutations found in BBS3 patients disrupt BBS3-BBSome interaction, but mutations found in nonsyndromic retinitis pigmentosa only partially decrease the interaction, highlighting the importance of BBS-BBSome interactions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, the functions of various centriolar satellite proteins diverge. Pcm1 and the BBSome promote ciliary membrane biogenesis and the trafficking of ciliary membrane proteins (18,21). Ofd1, on the other hand, appears to regulate ciliogenesis by recruiting components of the distal appendages and IFT particles, although a recent study appeared to suggest an additional negative role of Ofd1 in ciliogenesis (22,23).…”
mentioning
confidence: 99%